Online drug information platform for the public in Hong Kong—Review of local drug information use and needs. (June 2018) - Cheng, F.W.T.; So, S.W.K.; Fung, B.W.T.; Hung, W.H.; Lee, V.W.Y.
Highlights: Online platform providing patient-oriented drug information service is promising. The most common types of question was related to drug ingredients and indications. Medications used in cardiovascular diseases were the drugs of concerns. The need of different age groups and enquirer groups should be individualized. Abstract: Introduction: In view of the popularity of Internet usage in Hong Kong, an interactive web-based drug information platform entitled "Ask My Pharmacist – Online University Led drug Enquiry Platform" (AMPOULE) was launched in 2009 to better serve the needs of drug information in Hong Kong. This paper aimed to evaluate the utility of AMPOULE in improving drug-related knowledge among the public and to reassess the needs of the general public in Hong Kong. Methods: All enquiries sent via AMPOULE were reviewed. Demographic data, nature of questions and types of drug class covered were analyzed. The workload of pharmacists was examined with respect to the preparation time needed for the enquiry, the lag days to reply and also the timing of enquiry recipient. Results: 2122 enquiries were received from 2009 to 2017. Most enquirers were from Hong Kong (56.6%) and female gender (49.2%). 13% of the concerned subjects were aged over 61-year-old. The most frequent types of questions and medications covered were "Drug Ingredients and Indications" (28.0%) and Adverse Drug Reactions (26.8%) and "Cardiovascular Medication" (21.9%) respectively but these varied in different age groups or enquirer groups. The median time for preparation was 40.0 min (IQR: 25–65 min) while the median time lag was found to be 2.5 days (IQR: 1.0–5.0 days). The number of enquiries received was evenly distributed throughout the day except during 1:00 am to 9:00 am and 7:00 pm to 8:00 pm. Conclusion: AMPOULE has demonstrated that an online platform providing patient-oriented drug information service through the Internet is promising and further promotion is warranted. Current data suggested that the need of different age groups and enquirer groups are different and should therefore be individualized.